Content Analysis of Political Awareness in Mata Najwa’s Talkshow (Descriptive Qualitative Study on Students of Pancasila and Citizenship Education, Universitas Negeri Jakarta) - Nabila Aprilia; Muhammad Japar; Yuyus Kardiman (Department of Civic Education, 2021)
This study aims to analyze the content of political awareness in the Mata Najwa talk show which was shown in the October 2020 episode. This study uses a qualitative descriptive method with a content analysis approach. The primary data source was obtained from the talk show Mata Najwa for the October 2020 period. Secondary data were obtained from interviews with informants, namely students of Pancasila and Citizenship Education at the State University of Jakarta class 2017 who watched the Mata Najwa talk show and expert opinions. The results of the study show that the broadcasts presented by the Mata Najwa talk show raised socio-political issues that developed in the community into themes or topics of discussion. Through critical dialogue between resource persons, they provide knowledge and understanding of the reality that is happening. The speakers were presented from 2 camps, pros and cons as well as expert speakers in their fields according to the topic of discussion who were able to provide analysis and clarification of the problems being discussed. From the opinion of the informants, they can know and understand the rights and obligations as citizens in the topics discussed.